The heat shock protein 83 (Hsp83) is required for Raf-mediated signalling in Drosophila. - van der Straten, A (1997)
The heat shock protein Hsp90 has been shown to associate with various cellular signalling proteins such as steroid hormone receptors, src-like kinases and the serine/threonine kinase Raf. While the interaction between steroid hormone receptors and Hsp90 appears to be essential for ligand binding and activation of the receptors, the role of Hsp90 in Raf activation is less clear. We have identified mutations in the hsp83 gene, the Drosophila homologue of hsp90, in a search for dominant mutations that attenuate signalling from Raf in the developing eye. The mutations result in single amino acid substitutions in the Hsp83 protein and cause a dominant-negative effect on the function of the wild-type protein. We show that both wild-type and mutant forms of Hsp83 bind to the activated Drosophila Raf but the mutant Hsp83 protein causes a reduction in the kinase activity of Raf. Our results indicate that Hsp83 is essential for Raf function in vivo.